A mill can grind with water that is past: byzantine (self)rewriting, from Lope de Vega to Castillo Solórzano - Fernández Rodríguez, Daniel (Revista Chilena de Literatura, 2020)
This article has two main goals. Firstly, it will examine the influence of the Byzantine plot of Lope de Vega’s La viuda, casada y doncella and Guzmán el Bravo on two novellas by Castillo Solórzano: El bien hacer no se pierde (Noches de placer, 1631) and La ingratitud castigada (La quinta de Laura, 1649). Secondly, it will explore the (re)writing process of the latter novella, since Castillo Solórzano not only draws on the above-mentioned works, but also on two short stories of his own creation: La libertad merecida (Jornadas alegres, 1626) and Amor con amor se paga (Los alivios de Casandra, 1640).